2007
DOI: 10.1111/j.1083-6101.2007.00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Online Communication and Adolescent Well-Being: Testing the Stimulation Versus the Displacement Hypothesis

Abstract: The aim of this study was to contrast the validity of two opposing explanatory hypotheses about the effect of online communication on adolescents' well-being. The displacement hypothesis predicts that online communication reduces adolescents' well-being because it displaces time spent with existing friends, thereby reducing the quality of these friendships. In contrast, the stimulation hypothesis states that online communication stimulates well-being via its positive effect on time spent with existing friends … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
394
1
17

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(462 citation statements)
references
References 44 publications
35
394
1
17
Order By: Relevance
“…Some authors have observed that abusive use of Internet and online interactions entails individuals" spending time on Internet at the expense of other daily activities, which leads to a consequent isolation, academic impairment, and problems in family relationships. Therefore, the psychosocial well-being of the individual is threatened (Valkenburg & Peter, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have observed that abusive use of Internet and online interactions entails individuals" spending time on Internet at the expense of other daily activities, which leads to a consequent isolation, academic impairment, and problems in family relationships. Therefore, the psychosocial well-being of the individual is threatened (Valkenburg & Peter, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the use of e-mail or Instant Messaging may improve face-to-face interaction and promote users' well-being (Morgan & Cotten, 2003;Shaw & Gant, 2002;. For instance, using a sample of 1,210 Dutch teenagers between 10 and 17 years of age, Valkenburg and Peter (2007) found that Instant Messaging, which was mostly used to communicate with existing friends, is a significant predictor of users' subjective well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Hipoteza obogatitve (Kraut idr., 2002) pravi, da imajo največjo korist od spleta tisti, ki že imajo močna socialna omrežja in socialne veščine, po kompenzacijski hipotezi pa naj bi bila spletna komunikacija bolj koristna za socialno anksiozne in zavrnjene posameznike, saj ti manko stikov v svojem okolju kompenzirajo na spletu (Lee, 2009). Ugotovitve raziskav večinoma kažejo, da je komunikacija mladostnikov na spletu pozitivno povezana s kvaliteto njihovih medosebnih odnosov in časom, ki ga mladostniki preživijo s svojimi prijatelji, ter s tem potrjujejo hipotezo obogatitve in stimulacijsko hipotezo (Valkenburg in Peter, 2007;Lee, 2009). …”
Section: Odnosi Na Spletu In Izven Spletaunclassified
“…Ahn, 2012;Ellison idr., 2007;Valkenburg in Peter, 2007) preučevale povezanost odnosov na spletu in izven spleta v povezavi z različnimi konstrukti (npr. socialnim kapitalom, osebnostnimi lastnostmi, samopodobo, kvaliteto prijateljskih vezi, uporabo spleta), jih je le malo obravnavalo povezanost socialne sprejetosti v razredu in socialne sprejetosti na spletu.…”
Section: Namen Raziskaveunclassified